Student Preparedness for Emergency Remote Learning - Sande, Beverly; Kemp, Charles; Burnett, Camille; Moore, Jerrel (Theory & Practice in Rural Education, 2021)
The recent worldwide pandemic, COVID-19, pushed students of all ages to remote learning in a matter of days. This abrupt change in the mode of delivery of instruction affected students differently. The researchers share findings of a study conducted among university preservice education students from Texas and Ohio concerning students' preparedness for this drastic change. The study sought to identify and document recurring themes about the students' experiences of remote learning and to determine how significantly socioeconomic status (SES), sociocultural values (SCV), and socioemotional learning (SEL) aspects impacted students’ transition to remote learning at these universities. Implications for university instructors and ways to improve educational experiences during such unprecedented times are discussed.